Perancangan Media Kampanye Komunikasi Persuasif Dampak Pernikahan Dini Di Lombok Barat - Miyarta yasa; muhammad fathul azis (Jurnal SASAK : Desain Visual dan Komunikasi, 2019)
Marriage is identical with happiness, every couple who goes through marriage hopes that their marriage will go well. To achieve this requires readiness, both in terms of thinking and financial maturity. A good age according to experts, a person to get married is 25 years for men and 21 years for women. But unfortunately many in the marriage community occur at a very young age, which we often call early marriage. . Based on the National Population and Family Planning Agency (BKKBN) the number of child marriages (18 years and under) in Indonesia is increasing. Early marriages occur usually not based on mature considerations, but are more dominated by personal needs, family economic factors, educational factors, hereditary adat factors, and mental factors of adolescents. Persuasive communication is one of the effective communication methods to influence someone in this case persuasive communication with video media is expected to be able to influence the public to suppress underage marriages. Data collection methods in this case use the Design Thingking method. the design of public service video advertisements about the risk of early marriage in West Lombok is Soft Sell, namely the concept of conveying the contents of messages indirectly to the intended target audience, and also having a comedy or comedy genre concept in it. The concepts used to influence the audience include the choice of color, font and also every scene in the video. For the color itself the authors use bright colors, cheerful and pleasant, also the selection of fonts that look relaxed and light. so this public service ad is easy to remember and influences the target audience following the advice in the campaign video. Keywords: campaign, persuasive communication, early marriage.